Learning Speaking Strategies by ESP Learners in English for Theology Classroom to Enhancing Self-Efficacy - Palimbunga', Theo Dedy; Datu, Louise Pali’; Ma’tan, Merlina (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2023)
Speaking is a skill that requires learners to have good self-efficacy. Self-efficacy can influence the behavior of learners. Learners with high self-efficacy will learn speaking easily, but learners with low self-efficacy will face the difficulties. In this case, there were ESP learners who were afraid of mispronouncing, avoiding assignments, lacking enthusiasm, and lack of confidence. This study aimed to find out the speaking learning strategies used by ESP learners in enhancing self-efficacy in English for Theology Classroom. This research was conducted at Institut Agama Kristen Negeri (IAKN) Toraja using a qualitative descriptive method. Data were collected through semi-structured interviews and observation. It involved twenty one students as research informants. The data obtained were then analyzed using a qualitative descriptive approach. The results showed that the speaking learning strategies used by ESP Learners in enhancing self-efficacy were cognitive strategy, affective strategy, memory strategy, social strategy, and metacognitive strategy. Of the five strategies that can be found, the most widely or dominantly used strategies are cognitive strategy and affective strategy.